Financial management achieving financial statement auditability in the Department of Defense : report to congressional requesters. - United States. Government Accountability Office ([Washington, D.C.] : U.S. Govt. Accountability Office, 2009)
In 2004, we reported that DOD lacked a comprehensive and integrated strategic plan with key milestones, measures/metrics, accountability mechanisms, or cost estimates for achieving financial statement auditability. While the FIAR Plan identifies three goals for improving DOD financial information and achieving audit readiness, it does not contain the key elements of a strategic plan that we have previously reported as necessary for successful DOD business transformation. During our review of DOD's September 2008 FIAR Plan, we identified the following areas that the department needs to address to improve the FIAR Plan as a strategic and management tool: clear guidance is needed in developing and implementing improvement efforts; no clear baseline exists against which incremental progress can be measured; linkages between FIAR Plan goals and corrective actions and reported accomplishments are not always clear; clear results-oriented metrics for measuring and reporting incremental progress are needed, and accountability is not clearly defined or assigned and resources budgeted and consumed are not identified. We also identified recent actions the department is taking to begin to address many of the issues we have identified above.
Title from cover screen (GAO, viewed on May 19, 2009).
"May 2009."
"GAO-09-373."
Includes bibliographical references.
Keywords: United States. -- Department of Defense -- Accounting; United States. -- Department of Defense -- Management; United States. -- Department of Defense -- Auditing